Complications And Influence of Surgical Approaches of Fourth Ventricle Tumors in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Tumors of the fourth ventricle in children pose a particular surgical challenge due to the proximity of eloquent neural parenchyma in the region. The two most common surgical routes to the fourth ventricle are the transvermian and telovelar approaches.Objectives: The goal of this study was to characterize the complications and morbidity related to the surgical management of pediatric fourth ventricle tumorsMethods: this retrospective study includes 50 patients with 4th ventricle tumors from three centers (Dr.Saad Alwatry hospital, neurosurgical teaching hospital and Ghazi Al-Hriri hospital) in period from oct.2021 to oct.2022 . Preoperative imaging and clinical notes were reviewed to extract data on presenting symptoms, surgical techniques, and postoperative complications.Results: Across the whole series, the transvermian approach was more frequent than the telovelar approach (60% vs 40%). The most common postoperative deficit was cerebellar mutism syndrome (CMS12%), followed by new weakness (10%), cranial neuropathy (8%), and new gait abnormality/ataxia (6%). There was no significant difference in the rate of CMS between telovelar or transvermian approaches (p = 0.722).Conclusions: Surgical management of pediatric fourth ventricle tumors continue to evolve. CMS is enduringly the major postoperative complication in this patient Population.